PEMIKIRAN ILMU FALAK KYAI NOOR AHMAD SS - J., Jayusman (Ahkam: Jurnal Hukum Islam, 2014)
Kyai Noor Ahmad SS was a profound ahli falak (astronomer)in the Nahdhatul Ulama (NU) organization. His contributionin the field of astronomy led him to be a member of the authorsin the almanac of the committee of NU. He also contributed tothe decision of any policy made by Lajnah Falakiah NU, aninstitution which concerns with astronomy. His masterpiece,Nur al Anwar, is used as a reference by the Ministry of ReligiousAffairs in deciding the first and the last day of Ramadhan andthe first day of Zulhijjah. The thought of astronomers come upwith more or less similar method but kyai Noorâs thought isinteresting to investigated further due to his great experiencein working with astronomy.Kata kunci: Noor Ahmad SS, Awal Waktu Salat, Arah Kiblat,Awal Bulan Kamariah, Gerhana